Effect of Different Roofing Material on Body Weight and Feed Intake of Indigenous Sheep under Stall Feeding System - Khant, Malhar; Patel, Nitin R.; Modi, Rakesh J.; Wadhwani, Kishan N. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted to assess the effect of roof on body weight and feed intake of sheared and non-sheared sheep understall feeding system in the hot dry season. Adult dry indigenous sheep (24) were distributed randomly into two treatment groups, i.e.,T1: asbestos roof and T2: agro - net roof. Each treatment comprised of six sheared and six non-sheared animals. Sheep were providedwith total mixed ration in morning, afternoon and night individually. The bodyweight of sheared (31.87 ± 2.14, 31.96 ± 1.55 kg) andnon-sheared (32.16 ± 1.59, 32.42 ± 1.42 kg) animals was comparable between roof treatments. The experimental animals reared underagro-net roofed shelter consumed significantly (p
Keywords: Bodyweight; ,Feed and nutrient intake; Roof; Sheared and non-sheared sheep